The Antagonist Principle : John Henry Newman and the Paradox of Personality - Poston, Lawrence, 1938- (Book collections on Project MUSE., 2014)
"Drawing on biographical, historical, literary, and theological scholarship, this book considers the alternating roles of aggression and self-effacement in Newman's own personality and writing"--